Organic-inorganic composite binder as well as preparation method and application thereof

Through the use of organic-inorganic composite adhesive, the cracking of active substances caused by changes in the volume of silicon negative electrode in lithium-ion batteries is solved, the cycle stability and energy density of the battery are improved, and the power density and longer Cycle life.

CN119208533APending Publication Date: 2024-12-27UNIV OF SCI & TECH LIAONING
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411315288.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The volume of the silicon negative electrode material in lithium-ion batteries changes greatly during the deintercalation of lithium ions, resulting in cracking and crushing of active substances, affecting the cycle life and safety performance of the battery. The existing binders cannot effectively solve this problem.

Method used

Using an organic-inorganic composite adhesive, including inorganic adhesive, organic small molecule adhesive and organic adhesive, a three-dimensional network structure is formed by a polycarboxylic acid crosslinking agent, combining silicon powder and conductive agent to form a " A bonding agent that combines both hardness and softness to improve adhesion and interface compatibility.

Benefits of technology

This binder effectively deals with the problem of volume expansion of silicon negative electrodes, improves the energy density and power density of lithium-ion batteries, extends the cycle life, and maintains the integrity of the electrode structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208533A_ABST
    Figure CN119208533A_ABST
Patent Text Reader

Abstract

The invention discloses preparation of an organic-inorganic composite binder and application of the organic-inorganic composite binder in a silicon negative electrode of a lithium ion battery. The binder is prepared through in-situ thermal initiation, has good interfacial compatibility and high ionic conductivity and is of a three-dimensional network structure. According to the binder, an organic binder and an inorganic binder are cross-linked through an organic small molecule cross-linking agent to form a rigid-flexible three-dimensional network structure, the organic binder has the advantages of being good in flexibility, large in elasticity and high in adhesive force, and the silicon negative electrode is good in interfacial compatibility, high in ionic conductivity and large in rigidity after being compounded with the inorganic binder; the adhesive has good interfacial compatibility with silicon particles, can promote formation of a solid electrolyte interface film (SEI film) and reduce interface impedance, has excellent ionic conductivity, obviously improves mechanical properties and adhesive properties of the adhesive, effectively deals with stress generated by huge volume change of a silicon negative electrode, and improves the service life of the silicon negative electrode. Therefore, the cycle life and initial coulombic efficiency of the battery are improved, and the service life of the battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of binders and electrochemical techniques, and relates to an organic-inorganic composite binder and a preparation method and application thereof. Background Art

[0002] With the rapid development of the new energy vehicle industry, the market demand for improving lithium-ion battery technology is growing rapidly, and the development of high-energy-density lithium-ion batteries is imminent; currently, the commercial negative electrode of lithium-ion batteries is graphite-based negative electrode material. The theoretical specific capacity is 372mAh g -1 , the low theoretical specific capacity can hardly meet the current market demand. Silicon anode has wide sources, low cost, safety and environmental protection, low voltage platform and high theoretical specific capacity (4200mAh g -1 ), which is considered to be the most promising negative electrode material for lithium-ion batteries.

[0003] However, the commercialization of silicon negative electrodes faces huge challenges - more than 300% volume changes will occur during the process of lithium ion insertion and extraction. This huge volume change will induce a series of problems. First, the huge volume change will cause the active material to break and crush; silicon particles are separated from conductive additives and current collectors, and the contact between them is poor, which affects the cycle life and safety performance of the battery. Secondly, this huge volume expansion will lead to an increase in interfacial impedance. The first cycle of silicon lithiation will form an SEI film on its surface, which can prevent silicon particles from directly contacting the electrolyte and producing other side reactions. However, the huge expansion of the silicon particle volume will destroy the SEI film, and the silicon surface exposed to the electrolyte will re-form a new SEI film. Repeated rupture and regeneration consumes too much electrolyte and forms a very thick SEI film, while increasing the interfacial impedance and reducing the energy density and power density of lithium-ion batteries.

[0004] Among many solutions, binders are expected to successfully deal with the huge volume change problem of silicon negative electrodes due to their simple preparation process and low cost. The existing organic polymer binders on the market are used as silicon negative electrode lithium-ion battery binders due to their good mechanical properties and viscoelasticity. However, a single organic polymer binder cannot effectively solve the problems currently faced by the commercialization of silicon negative electrodes. Moreover, silicon is a semiconductor material with low electrical conductivity and poor electrochemical kinetic performance in lithium-ion batteries. Inorganic binders have good interface compatibility with silicon negative electrodes. While improving adhesion, they can promote the formation of a stable SEI film, reduce interface impedance, and have excellent ionic conductivity. However, due to their high brittleness and strong rigidity, it is difficult to solve the huge volume expansion problem of silicon negative electrodes, thereby limiting their application in high energy density and high power density batteries. Therefore, there is an urgent need to develop a new type of binder to promote the development of lithium-ion batteries. Summary of the invention

[0005] In view of the problems of poor mechanical properties, poor adhesion, poor interface compatibility, and low ion conductivity of existing binders, the present invention aims to propose an organic-inorganic composite binder and its preparation method and application, which can effectively deal with a series of problems such as the huge volume expansion of silicon negative electrode and the shedding of active substances caused by expansion, and the continuous rupture of SEI film leading to increased interface impedance; at the same time, the binder can also improve the ion conductivity of silicon negative electrode materials and improve the power density of silicon negative electrode lithium ion batteries. The silicon negative electrode lithium ion battery prepared by the binder has the advantages of high energy density and power density and good cycle stability.

[0006] In order to achieve the above object, the present invention is solved by the following technical solutions:

[0007] An organic-inorganic composite binder, characterized in that it comprises an inorganic binder, an organic small molecule binder, an organic binder, silicon powder, and a conductive agent, wherein the organic small molecule cross-linking agent is a polycarboxylic acid, and the organic binder is a water-soluble polymer compound.

[0008] Furthermore, the inorganic binder is at least one of silicate, phosphate and borate.

[0009] Furthermore, the organic small molecule binder is at least one of citric acid, tannic acid, oxalic acid and phytic acid.

[0010] Furthermore, the organic binder is at least one of carboxymethyl cellulose salt, alginate, polyacrylic acid, and polyacrylamide.

[0011] The present invention also provides a method for preparing an organic-inorganic composite binder, comprising the following steps:

[0012] S1) dissolving an organic small molecule binder and an organic binder in deionized water, and stirring at room temperature for 0.5 to 1 hour to form a stable and uniform mixed solution;

[0013] S2) adding deionized water to the inorganic binder, stirring at room temperature for 0.5 to 1 hour, mixing evenly to form a uniform and stable solution;

[0014] S3) adding the solution in S2) to the mixed solution in S1) and stirring at room temperature for 3 hours to obtain a binder;

[0015] S4) Silicon powder, a binder and a conductive agent are mixed in a mass ratio of 8:1:1, ground in a mortar for 20 to 30 minutes, and then coated on a copper current collector, dried in a vacuum oven at 80° C. for 12 hours, and then cross-linked at 60 to 150° C. for 6 hours to obtain a silicon-based negative electrode sheet.

[0016] Furthermore, the mass ratio of the inorganic binder, the organic small molecule binder, and the organic binder is 2-6:2:0-7.

[0017] The present invention also provides a lithium ion battery silicon-based negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer deposited on the surface of the negative electrode current collector, and the negative electrode material layer is made of the above-mentioned organic-inorganic composite binder.

[0018] Beneficial Effects

[0019] Compared with the existing technology, this technology has the following beneficial effects:

[0020] A method for preparing an organic-inorganic composite binder, wherein the binder is prepared by a "one-pot method" and an organic binder and an inorganic binder are in situ thermally initiated by a small molecule organic crosslinking agent to form a "rigid and flexible" three-dimensional network structure. The binder prepared by the above method has the advantages of safety and environmental protection, and the preparation process and application fields meet safety and environmental protection standards. The entire preparation process is simple, low-cost, and highly repeatable, and can be actually applied in actual production.

[0021] An organic-inorganic composite binder, which forms a three-dimensional network structure by cross-linking an inorganic binder liquid silicate and an organic binder sodium carboxymethyl cellulose through an organic small molecule cross-linking agent citric acid. This network not only has the characteristics of good flexibility, high elasticity and strong viscosity of common organic binders, but also has the characteristics of good interfacial compatibility between the inorganic binder silicate and silicon particles, which can promote the formation of a stable SEI film while improving adhesion. In addition, the liquid silicate undergoes a hydration reaction, which can provide a transmission site for the transport of lithium ions, promote the transport of lithium ions during the charge and discharge process of a silicon negative electrode lithium battery, and improve the rate performance of the lithium ion battery.

[0022] An application of an organic-inorganic composite binder has been verified and found that the battery using the binder has a good improvement in charge and discharge cycle stability, which is specifically manifested in that the battery capacity remains stable as the number of cycles increases. This is because the organic binder component in the binder disclosed in the present invention contains a large number of carboxyl and hydroxyl functional groups, and a large number of hydrogen bonds are formed, which can interact with silicon particles and current collectors to improve adhesion; and the inorganic binder component liquid silicate and silicon particles can enhance the "diffusion" phenomenon due to the "like dissolves like" principle, and further enhance the adhesion ability, so that this binder can well deal with the problem of irreversible volume expansion of silicon particles, improve the cycle life of the battery, and the charge and discharge efficiency, and this liquid silicate hydration reaction provides a transmission site for lithium ions, promotes the transportation of lithium ions, and its good interfacial compatibility can promote the formation of a stable SEI film, so that the first week coulomb efficiency and rate performance of the negative electrode are greatly improved. After continuous charge and discharge, the electrode structure can still be kept intact, and the electrode thickness changes are also small. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 180° peeling test of Example 1 of the present invention and Comparative Examples 1, 2, and 3;

[0024] Figure 2 The first cycle charge-discharge curves and coulombic efficiencies of Example 1 of the present invention and Comparative Examples 1, 2, and 3;

[0025] Figure 3 For example 1 to example 5 of the present invention at 2A g -1 Long cycle performance test of 200 cycles under current density;

[0026] Figure 4 For example 1, example 6 and example 7 of the present invention at 1A g -1 Long cycle performance test of 100 cycles at a current density of

[0027] Figure 5 For Example 1 of the present invention and Comparative Examples 1, 2, and 3 at 1A g -1 Performance test of long cycle of 250 cycles under current density;

[0028] Figure 6 The surface morphology of the electrodes of Example 1 of the present invention and Comparative Examples 1, 2, and 3 were taken by scanning electron microscope before and after 250 cycles. DETAILED DESCRIPTION

[0029] The following is a further description of the present invention. These examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0030] The invention discloses an organic-inorganic composite binder, a method for preparing the organic-inorganic composite binder, and application of a silicon negative electrode sheet prepared by using the organic-inorganic composite binder. The negative electrode comprises a copper current collector and a negative electrode active material wrapped on the current collector, a conductive agent and a binder. The negative electrode active material is a silicon-based material. The conductive agent is selected from any one of carbon black, graphite, carbon nanotubes, graphene or composite conductive agents composed of the same, or any one of conductive polymer binders.

[0031] Organic-inorganic composite binder, a polymer binder with a three-dimensional network structure formed by cross-linking an inorganic binder and an organic binder with an organic small molecule binder, wherein the organic small molecule binder includes any one or a combination of citric acid, oxalic acid, acrylic acid, tannic acid or a composite polymer composed of these, the organic binder includes but is not limited to any one or more of sodium carboxymethyl cellulose, sodium alginate, polyacrylic acid or other water-based polymer binders containing carboxyl and hydroxyl groups, mixed in different proportions, and the inorganic binder includes one or more composites of silicates, phosphates, borates or other inorganic binders.

[0032] Organic binders have good viscoelasticity and flexibility, and contain a large number of functional groups such as hydroxyl and carboxyl groups, which can form intermolecular hydrogen bonds, improve adhesion, and thus improve the ability to cope with irreversible damage caused by volume changes of silicon negative electrodes. Inorganic binders use the principle of "like dissolves like" to promote the "diffusion" effect between molecules, which can not only improve adhesion, but also good interfacial compatibility can promote the formation of a stable SEI film and inhibit the increase in interfacial impedance caused by the volume expansion of silicon particles; in addition, inorganic binder liquid silicate can also provide transmission sites for lithium ions, promote the transportation of lithium ions, and improve lithium ion conductivity; organic small molecule crosslinkers crosslink the above two together to form a three-dimensional network structure, using the high rigidity of inorganic binders and the good flexibility of organic binders to form a "rigid and flexible" structure, thereby improving the mechanical properties of the binder. The binder combines the functions of the inorganic binder with the functions of the organic binder, greatly improving the performance of the binder.

[0033] The invention discloses an application of an organic-inorganic composite binder in a lithium-ion battery. When the negative electrode of the lithium-ion battery prepared by the binder is used to assemble a lithium-ion half-cell for testing, the counter electrode is lithium metal, the electrolyte is a mixed solution of lithium hexafluorophosphate, dimethyl carbonate and diethyl carbonate, and contains 10-25 vol% of fluoroethylene carbonate as an additive, and the diaphragm is a polypropylene microporous diaphragm, wherein the concentration of lithium hexafluorophosphate in the electrolyte is 0.5-2 mol·L -1 Compared with silicon negative electrode lithium ion batteries prepared using the binder disclosed in the present invention, silicon negative electrode lithium ion batteries prepared using the commercial binder CMC have higher charge and discharge capacity, longer cycle life and better rate performance.

[0034] The following will be described in conjunction with specific embodiments and comparative examples:

[0035] Example 1

[0036] An organic-inorganic composite binder is prepared in the following manner:

[0037] Take 2 mg of citric acid and 6 mg of sodium carboxymethyl cellulose, dissolve them in 1200 μL of water, and stir at room temperature for 0.5 hour until they are completely dissolved.

[0038] Take 10 μL of 20 wt % lithium polysilicate solution, the mass ratio of lithium polysilicate to citric acid and sodium carboxymethyl cellulose is 2:2:6, add 200 μL of water, stir for 0.5 hour, and dilute evenly.

[0039] The lithium polysilicate solution was added to a mixed aqueous solution of citric acid and sodium carboxymethyl cellulose, and stirred at room temperature for 3 hours to obtain a binder, which was recorded as CCL.

[0040] Weigh silicon powder and conductive agent Super P in a mortar, and put the prepared binder into the mortar at a mass ratio of 8:1:1. Grind for 20 minutes to obtain silicon negative electrode slurry. Then use a coating machine to coat the silicon negative electrode slurry on copper foil with a loading of 1.3 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 100°C for 6 hours to cross-link citric acid, sodium carboxymethyl cellulose and lithium polysilicate to form a three-dimensional network structure.

[0041] The copper foil was transferred to a glove box filled with argon to assemble a 2025 button half-cell for testing. The diaphragm is a polypropylene microporous diaphragm. The packaged battery was left aside for 12 hours and a constant current charge and discharge test was performed at a voltage range of 0.01 to 1.5 V. The test steps were to discharge the battery to 0.01 V at a constant current in the blue battery test system, then charge it to 1.5 V at a constant current, and cycle the test for 100 to 250 cycles to test the cyclic electrochemical performance of the battery.

[0042] Example 2

[0043] Take 2 mg of phytic acid and 6 mg of sodium carboxymethyl cellulose, dissolve them in 1200 μL of water, and stir at room temperature for 1 hour until they are completely dissolved.

[0044] Take 10 μL of 20 wt % lithium polysilicate solution, the mass ratio of lithium polysilicate to phytic acid and sodium carboxymethyl cellulose is 2:2:6, add 200 μL of water, stir for 1 hour, and dilute evenly.

[0045] The lithium polysilicate solution was added to a mixed aqueous solution of phytic acid and sodium carboxymethyl cellulose, and stirred at room temperature for 3 hours to obtain a binder, which was recorded as PVA-CL.

[0046] Weigh silicon powder and conductive agent Super P in a mortar, and add the prepared binder into the mortar at a mass ratio of 8:1:1. Grind for 30 minutes to obtain silicon negative electrode slurry. Then use a coating machine to coat the silicon negative electrode slurry on copper foil with a loading of 1.2 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 60°C for 6 hours to cross-link phytic acid, sodium carboxymethyl cellulose and lithium polysilicate to form a three-dimensional network structure.

[0047] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0048] Example 3

[0049] Take 2 mg of citric acid and 6 mg of polyacrylic acid, dissolve them in 1200 μL of water, and stir at room temperature for 0.5 hour until they are completely dissolved.

[0050] Take 10 μL of 20 wt % lithium polysilicate solution, where the mass ratio of lithium polysilicate to citric acid and polyacrylic acid is 2:2:6, add 200 μL of water, stir for 1 hour, and dilute evenly.

[0051] The lithium polysilicate solution was added to a mixed aqueous solution of citric acid and polyacrylic acid, and stirred at room temperature for 3 hours to obtain a binder, which was recorded as PAA-CL.

[0052] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared binder into the mortar and grind for 30 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1.23 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 80°C for 6 hours to cross-link citric acid, polyacrylic acid and lithium polysilicate to form a three-dimensional network structure.

[0053] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0054] Example 4

[0055] Take 2 mg of citric acid and 6 mg of polyacrylamide, dissolve them in 1200 μL of water, and stir at room temperature for 1 hour until they are completely dissolved.

[0056] Take 10 μL of 20 wt % lithium polysilicate solution, the mass ratio of lithium polysilicate to citric acid and polyacrylamide is 2:2:6, add 200 μL of water, stir for 0.5 hour, and dilute evenly.

[0057] The polysilicate lithium solution was added to a mixed aqueous solution of citric acid and polyacrylamide, and stirred at room temperature for 3 hours to obtain a binder, which was recorded as PAM-CL.

[0058] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared binder into the mortar and grind for 20 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1.21 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 150°C for 6 hours to cross-link citric acid, polyacrylamide and lithium polysilicate to form a three-dimensional network structure.

[0059] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0060] Example 5

[0061] Take 2 mg of citric acid, dissolve it in 200 μL of water, and stir it at room temperature for 0.5 hour until it is completely dissolved.

[0062] Take 10 μL of a 20 wt % lithium polysilicate solution, where the mass ratio of lithium polysilicate to citric acid is 2:2, add 800 μL of water, stir for 0.5 hours, and dilute evenly.

[0063] The polysilicate lithium solution was added to the aqueous solution of citric acid, and then 200 μL of poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) was added, and stirred at room temperature for 3 hours to obtain a binder, which was recorded as PEDOT-CL.

[0064] Weigh silicon powder in a mortar with a mass ratio of silicon powder to binder of 8:1. Then add the prepared binder into the mortar and grind for 20 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil with a loading of 1.1 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 100°C for 6 hours to cross-link citric acid, poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) and lithium polysilicate to form a three-dimensional network structure.

[0065] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0066] Poly(3,4-ethylenedioxythiophene)-poly(styrene sulfonate) is a water-based binder and a conductive agent.

[0067] Example 6

[0068] Take 2 mg of citric acid and 2 mg of sodium carboxymethyl cellulose, dissolve them in 1200 μL of water, and stir at room temperature for 1 hour until they are completely dissolved.

[0069] Take 30 μL of 20 wt % lithium polysilicate solution, where the mass ratio of lithium polysilicate to citric acid and sodium carboxymethyl cellulose is 6:2:2, add 200 μL of water, stir for 1 hour, and dilute evenly.

[0070] The lithium polysilicate solution was added to a mixed aqueous solution of citric acid and sodium carboxymethyl cellulose, and stirred at room temperature for 3 hours to obtain a binder, which was designated as CCL-2.

[0071] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared binder into the mortar and grind for 20 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1.2 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 100°C for 6 hours to cross-link citric acid, sodium carboxymethyl cellulose and lithium polysilicate to form a three-dimensional network structure.

[0072] The silicon negative electrode sheet was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0073] Example 7

[0074] Take 2 mg of citric acid and 7 mg of sodium carboxymethyl cellulose, dissolve them in 1200 μL of water, and stir at room temperature for 0.7 hours until they are completely dissolved.

[0075] Take 5 μL of 20 wt % lithium polysilicate solution, the mass ratio of lithium polysilicate to citric acid and sodium carboxymethyl cellulose is 1:2:7, add 200 μL of water, stir for 0.7 hours, and dilute evenly.

[0076] The liquid lithium polysilicate solution was added to a mixed aqueous solution of citric acid and sodium carboxymethyl cellulose, and stirred at room temperature for 3 hours to obtain a binder, which was recorded as CCL-4.

[0077] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared binder into the mortar and grind for 15 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1.35 mg cm -2, placed in a vacuum oven, dried at 80°C for 12 hours, and cross-linked at 100°C for 6 hours to cross-link citric acid, sodium carboxymethyl cellulose and lithium polysilicate to form a three-dimensional network structure.

[0078] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0079] Comparative Example 1

[0080] Take 5 mg of citric acid, dissolve it in 1200 μL of water, and stir it at room temperature for 0.5 hour until it is completely dissolved.

[0081] Take 25 μL of a 20 wt % lithium polysilicate solution, where the mass ratio of lithium polysilicate to citric acid is 5:5, add 200 μL of water, stir for 0.5 hour, and dilute evenly.

[0082] The lithium polysilicate solution was added to the aqueous solution of citric acid and stirred at room temperature for 3 hours to obtain a binder, which was recorded as CL.

[0083] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared silicon negative electrode binder into the mortar and grind for 20 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1 mg cm -2 , placed in a vacuum oven, dried at 80°C for 12 hours, and kept at 100°C for 6 hours to cross-link citric acid and lithium polysilicate to form a three-dimensional network structure.

[0084] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0085] Comparative Example 2

[0086] Take 10 mg of sodium carboxymethyl cellulose, dissolve it in 1200 μL of water, and stir it at room temperature for 3 hours until it is completely dissolved to obtain a binder, which is recorded as CMC.

[0087] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared binder into the mortar and grind for 30 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1.2 mg cm -2 , placed in a vacuum oven, dried at 80℃ for 12 hours and kept at 100℃ for 6 hours.

[0088] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0089] Comparative Example 3

[0090] Take 50 μL of 20 wt% lithium polysilicate solution, dissolve it in 1200 μL of water, and stir it at room temperature for 3 hours until it is stirred evenly to obtain a binder, which is recorded as LS.

[0091] Weigh silicon powder and conductive agent Super P in a mortar. The mass ratio of silicon powder, conductive agent and binder is 8:1:1. Then add the prepared binder into the mortar. Add 100 μL of isopropanol as a dispersant for the conductive agent. Grind for 20 minutes to obtain silicon negative electrode slurry. Then use a coater to coat the slurry on copper foil. The loading amount is 1.1 mg cm -2 , placed in a vacuum oven, dried at 80℃ for 12 hours and kept at 100℃ for 6 hours.

[0092] The copper foil was transferred to a glove box filled with argon gas to assemble a 2025-type button half-cell for testing. All steps were the same as in Example 1.

[0093] Performance evaluation method

[0094] 180° peel test

[0095] The electrode peel strength was tested according to the national standard GB2792 (peeling test was performed on the silicon negative electrode sheets of the above embodiment 1 and comparative examples 1, 2, and 3). Figure 1 , the average peel force is shown in the following table:

[0096]

[0097]

[0098] Cyclic performance test

[0099] Use an electrochemical workstation to perform constant current charge and discharge tests on the battery. The results are as follows Figure 2 , Figure 3 , Figure 4 ,in Figure 2 The first charge-discharge curves and first cycle coulombic efficiency of Example 1 and Comparative Examples 1, 2, and 3 show that CCL has a longer discharge platform and a higher first cycle discharge capacity (2700 mAh g -1 ), and the first coulombic efficiency can reach 93%, which is much higher than 85%, 89% and 87% of comparative examples 1, 2 and 3. Figure 3 The constant current charge and discharge tests of Examples 1, 2, 3, 4, and 5 show that the discharge specific capacity of Example 1 is 2A g -1 The current density remains at 1480 mAh g after 200 cycles. -1The discharge specific capacity of Examples 1-5 after 200 cycles is 74.67%, 50.41%, 66.79%, 51.37%, 37.42%, 87.29% and 76.66% respectively. We found that Example 1 has the best effect. We explored the ratio of the three substances in Example 1. Figure 4 For Examples 1, 6, and 7 at 1A g -1 Through a long cycle test of 100 cycles at a current density of , we found that when the CMC addition ratio was 6, the electrochemical performance of the binder was the best. That is, Example 1. Figure 5 This is the constant current charge and discharge test of Example 1 and Comparative Examples 1, 2, and 3. Example 1 at 1A g -1 The current density can be cycled for 250 cycles and still maintain 2200mAh g -1 This shows that Example 1 can effectively suppress the volume expansion of the silicon negative electrode and maintain the good energy density and power density of the silicon negative electrode lithium-ion battery.

[0100] Scanning electron microscope test

[0101] By scanning the electrode surface of the binder silicon negative electrode sheet of the present invention before and after 250 cycles, it can be clearly seen that the binder disclosed in the present invention can well maintain the stability of the electrode surface with fewer cracks.

[0102] It can be seen from the above results that the embodiments of the present invention achieve the following technical effects:

[0103] The organic-inorganic composite binder disclosed in the present invention utilizes an organic small molecule cross-linking agent to cross-link an organic binder and an inorganic binder in situ to form a rigid and flexible three-dimensional network water-soluble polymer binder, which has good flexibility and good viscoelasticity of organic polymers, and has a large number of hydroxyl and carboxyl functional groups, which can form a large number of hydrogen bonds, improve adhesion, and enable the binder to cope well with the irreversible crushing and falling off caused by the expansion of the silicon negative electrode, resulting in the problem of reduced battery capacity. It also has the characteristics of good interfacial compatibility of the inorganic binder, which can promote the formation of a stable SEI film, and can promote the "diffusion" effect. According to the "like dissolves like" principle, the adhesive ability of the binder to silicon particles is improved, and the crushing and falling off of the silicon negative electrode are suppressed. In addition, the oxygen anions on the inorganic binder can provide transmission sites for the transportation of lithium ions, promote the transportation of lithium ions, improve ionic conductivity, and improve the rate performance of the battery. In addition, the inorganic binder has strong rigidity and combines with the organic binder to form a three-dimensional network structure that is both rigid and flexible: the organic binder in the flexible segment can provide adhesion and self-repairing ability, and the inorganic binder in the rigid segment can maintain the structure from being easily damaged, buffering the huge stress generated by the volume expansion of the silicon negative electrode. Therefore, the binder disclosed in the present invention can not only cope with the huge volume expansion generated during the charging and discharging of the silicon negative electrode, as well as a series of problems caused by the volume expansion, and improve the battery cycle life, but also improve the rate performance of the battery.

[0104] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the above embodiments can be changed, modified, replaced and deformed within the scope of the present invention. Any modification, equivalent replacement and improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An organic-inorganic composite binder, characterized in that: The invention comprises an inorganic binder, an organic small molecule cross-linking agent, a water-based binder, silicon powder and a conductive agent, wherein the organic small molecule cross-linking agent is a polycarboxylic acid and the water-based binder is a water-soluble polymer compound.

2. The organic-inorganic composite binder according to claim 1, characterized in that: The inorganic binder is at least one of silicate, phosphate and borate.

3. The organic-inorganic composite binder according to claim 1, characterized in that: The organic small molecule cross-linking agent is at least one of citric acid, tannic acid, oxalic acid and phytic acid.

4. The organic-inorganic composite binder according to claim 1, characterized in that: The water-based binder is at least one of carboxymethyl cellulose salt, alginate, polyacrylic acid and polyacrylamide.

5. A method for preparing an organic-inorganic composite binder, characterized in that: The following steps are involved: S1) dissolving an organic small molecule cross-linking agent and an aqueous binder in deionized water, and stirring at room temperature for 0.5 to 1 hour to form a stable and uniform mixed solution; S2) adding deionized water to the inorganic binder, stirring at room temperature for 0.5 to 1 hour, mixing evenly to form a uniform and stable solution; S3) adding the solution in S2) to the mixed solution in S1) and stirring at room temperature for 3 hours to obtain a binder; S4) Silicon powder, a binder, and a conductive agent are mixed in a mass ratio of 8:1:1, ground in a mortar for 20 to 30 minutes, and then coated on a copper current collector, dried in a vacuum oven at 80° C. for 12 hours, and then cross-linked at 60 to 150° C. for 6 hours to obtain an organic-inorganic composite binder.

6. The method for preparing an organic-inorganic composite binder according to claim 5, characterized in that: The mass ratio of the inorganic binder, the organic small molecule cross-linking agent and the water-based binder is 2-6:2:0-7.

7. A lithium-ion battery silicon-based negative electrode sheet, characterized in that: It comprises a negative electrode current collector and a negative electrode material layer deposited on the surface of the negative electrode current collector, and the negative electrode material layer is made of the organic-inorganic composite binder according to any one of claims 1 to 4.

Citation Information

Cited By

  • Sliding plate brick and preparation method thereof

    CN120004602A

  • Polluted soil solidification and stabilization treatment agent for repairing rare earth mine and preparation method

    CN122479726A

  • A rare earth mine repair contaminated soil solidification and stabilization treatment agent and a preparation method thereof

    CN122479726B